Report for the period July 2009 - Dec 2009 : (culture, gender, youth and sport) (CCS [Georgetown]GY, 2010)
Highlights the Directorate's activities in the fields of culture, gender, youth and sport during the period indicated.
Prepared for H. E. Drs Runaldo R. Venetiaan...in preparation for the Twenty-First Inter-sessional Meeting of the Conference of Heads of Government, Dominica, 11-12 March, 2010